PEMANFAATAN MEDIA SOSIAL WHATSAPP SEBAGAI MEDIA BELAJAR TAHSIN AL QUR’AN PADA PROGRAM BETTA QUR’AN - Ahmad Adnan; Ahmad Yadi Mulya (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
The research was conducted to analyze the utilization of Whatsapp social media as a medium for learning Al-Qur'an Tahsin in the Betta Qur'an program. This research is qualitative research with a case study approach. The data collection technique is through observation/direct observation of the BETTA Qur'an program. The conclusion of the study found that the use of WhatsApp social media in the BETTA Qur'an program as a medium for conveying material reached 50% of the 20 respondents, apart from that WhatsApp could also be used as a medium for talaqqi and evaluation of members' reading of the Qur'an whose percentage reached 5%. up to 45%, with the help of WhatsApp's free features such as images, audio recordings, videos, and sending documents.